Metal Matrix Composite Brake Rotor: Historical Development and Product Life Cycle Analysis - M. M., Rahman; A. A., Adebisi; M. A., Maleque (Universiti Malaysia Pahang, 2011)

(untitled)
Metal matrix composites (MMCs) have become attractive for engineering structural applications due to their excellent specific strength property and are increasingly seen as alternative to the conventional materials particularly in the automotive industry. In this study, a historical background on the development and application of metal matrix composite for automotive brake rotor is presented. The discussion also includes analysis of the product life cycle with stir casting as a case study. The historical review analysis revealed that gradual development of material and processing technique have lead to a lighter weight, lower cost, and higher performance brake rotor as a result of the better understanding of the mechanics of metal matrix composite. It emerged from the study that stir casting technique provides ease of operation, sustainability and most significantly very competitive without sacrificing quality relative to other techniques; and as such is the most attractive manufacturing process in the industry. These findings can be used for future design and manufacture of an efficient and effective aluminium matrix composite brake rotor for automotive and other applications.